Underutilization of Anticoagulant for Venous Thromboembolism Prophylaxis in Three Hospitals in Jakarta - T. Djumhana Atmakusuma; Karmel L Tambunan; Lugyanti Sukrisman; Shufrie Effendi; Andhika Rachman; Arini Setiawati; Ikhwan Rinaldi (Interna Publishing, 2016)
Aim: to assess the current use of anticoagulants and implementation of International Guidelines in venous thromboembolism (VTE) prophylaxis in hospitalized patients with acute medical illnesses in Jakarta, Indonesia. Methods: a multicenter, prospective, disease registry, recruiting patients diagnosed as acutely ill medical diseases and other medical conditions at risk of VTE, with in-hospital immobilization for at least 3 days. Results: of 401 patients, 46.9% received anticoagulants which included unfractionated heparin (64.4%), fondaparinux (11.7%), enoxaparin (9.6%), warfarin (3.7%), and combination of anticoagulants (10.6%). VTE prophylaxis using physical and mechanical method was used in 81.3% of patients, either as a single modality or in combination with anticoagulants. During hospitalization, VTE were found in 3.2% patients; 10 patients (2.5%) had lower limb events and 3 patients (0.75%) had a suspected pulmonary embolism. The main reference international guidelines used were AHA/ASA 2007 (47.4%), followed by ACCP 2008 (21.7%). Conclusion: the study showed underutilization of prophylaxis anticoagulants in which mechanical thromboprophylaxis either alone or combination with anticoagulants was the most commonly used. Unfractionated heparin was the preferable choice. The most commonly used guideline was AHA/ASA 2007. VTE thromboprophylaxis in medically ill patients needs to be encouraged. Key words: venous thromboembolism (VTE), prophylaxis, registry, non-surgery hospitalization.